Photography and digital media: the bloger’s universe in the creative construction of tourist destinations Fotografia e mídia digital: o universo blogueiro na construção criativa de destinos turísticos - Silvia Oliveira (Discursos Fotográficos, 2007)
Analyses the discourse held in Voyage blogs through texts and pictures. It measures the influence of such digital media in building the tourist image reality. It shows how the scenario construction is ensured by daily publication in blogs. It seeks to point out discursive ant thematic strategies concerning the tourism portrait through photography. It discusses the movement of ideas within the blogosphere. Analisa o discurso conduzido pelos blogs de viagem através de textos e fotos. Verifica a influência dessa mídia digital na construção da realidade da imagem turística. Mostra como é feita a construção de cenários através da publicação cotidiana nos blogs. Busca apontar estratégias discursivas e temáticas, relacionadas ao retrato do turismo através da fotografia. Discute o movimento das idéias em torno da blogosfera.